Production and Characterization of Energy Materials with Adsorbent Properties by Hydrothermal Processing of Corn Stover with Subcritical H2O - Machado, N.T.; Castro, D.A.R. de; Queiroz, L.S.; Santos, M.C.; Costa, C.E.F. da (Journal of Applied Solution Chemistry and Modeling, 2016)
This work aims to investigate the effect of temperature on the process performance of hydrothermal processing (HTC) of corn Stover with subcritical H2O and on the morphology of solid products. The experiments were carried out at 200, 225 and 250 ºC, reaction time of 240 minutes, heating rate of 2.0 ºC/min, and biomass to water ratio of 1:10, using a pilot scale stirred tank reactor (STR) of 5 gallon, operating in batch mode. The process performance analyzed by computing the yields of solid and liquid reaction products (RLP). The aqueous phase (H2O + RLP) was physicochemical analyzed for pH and total carboxylic acids, expressed as total acetic acid content. The chemical compositions of carboxylic acids, furfural, and hydroxymethylfurfural (HMF) in the aqueous phase determined by GC-MS and HPLC. The results showed solid yields ranging from 57.39 to 35.82% (wt.), and liquid reaction products (RLP) yields ranging from 39.53 to 54.59% (wt.). The solid phase products were characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). The chemically activated (2.0 M NaOH) solid phase energy material obtained by HTC at 250 °C, applied as adsorbent to investigate the capacity and/or efficiency to adsorb acetic acid from 1.0 to 4.0 g/L model solutions at 25 °C. The solid phase yield decreases along with the temperature, showing an inflection region between 200 and 225 °C, whereas a drastic change takes place, while that of liquid phase increases, showing also a drastic change between 200 and 225 °C. The total acetic acid content of aqueous phase varied from 4064 to 5387 mg/L, while the pH from 3.77 to 3.91. The GC analysis identified the presence of volatile carboxylic acids, particularly acetic acid, in concentrations between 4020 and 5040 mg/L. HPLC identified the presence of furfural and hydroxymethylfurfural, whose concentrations decrease exponentially and linearly along with the temperature between 686.7 and 0.0, and 443.9 and 0.0 mg/L, respectively, being both compounds not detectable at 250 °C. The elemental/ultimate analysis of solid products shows that carbon content increases, while the oxygen and hydrogen contents decrease, along with the temperature. The H/C and O/C ratios decrease linearly as process temperature increases, and the high heating value (HHV) of solid reaction products, an energy densified material, changes sharply between 200 and 225 °C, showing an increase with temperature. The SEM, EDX, and XDR indicates a change on the morphology and mineralogical phases present in solid reaction products with temperature, particularly at 250 °C. The activated solid phase has proven to be very selective to adsorb acetic acid, showing that recovery of acetic acid from hydrothermal carbonization/liquefaction aqueous solutions is feasible by using a multistage-stage adsorption process in series.